2020
DOI: 10.3389/fneur.2020.00338
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease Associated With Morning Glory Disc Anomaly and Other Ophthalmic Findings: A Mini-Review

Abstract: Moyamoya disease (MMD) is a chronic cerebrovascular disease that frequently results in intracranial ischemia or hemorrhage. Its concurrence with varying ophthalmic findings is relatively rare yet may lead to irreversible blindness. We performed a search and review of the literature to characterize the relevance of MMD (excluding moyamoya syndrome) and ophthalmic findings. As a result, a total of 38 articles identified from PubMed and Web of Science were included in this mini-review. Patients with MMD sometimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…1,11,29 Furthermore, MMD is a condition in which stenosis and occlusion of the ICA progress, and the primary site of manifestation is near the ophthalmic artery; therefore, retinal vascular alterations are possible. 10,[30][31][32][33] However, changes in the retinal vessels may not be significant in young individuals due to their ability to endure ischemic stress. 14 In addition, early signs of retinal vessel alterations due to MMD may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,29 Furthermore, MMD is a condition in which stenosis and occlusion of the ICA progress, and the primary site of manifestation is near the ophthalmic artery; therefore, retinal vascular alterations are possible. 10,[30][31][32][33] However, changes in the retinal vessels may not be significant in young individuals due to their ability to endure ischemic stress. 14 In addition, early signs of retinal vessel alterations due to MMD may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Moyamoya disease is associated with MGDA, retinal vascular occlusion, visual field defects caused by ischemia or hemorrhage, optic disc abnormalities, etc. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of the ICA was found in 10 (76.9%) patients. 19 The pathological changes involving the optic disc and intracranial arteries are suggestive of a similar deficiency during ectoderm development in both diseases. 19 Taking into account of the possibility of MMD as a vascular form of cephalic neurocristopathy, 13 the coexistence of MMD and these congenital abnormalities within the region of cephalic NCC distributions reflects the common underlying common pathomechanism, that is, a subtype of cephalic neurocristopathy.…”
Section: Cephalic Neurocristopathymentioning
confidence: 99%
“…17,18 Wang et al reported morning glory disc anomaly (MGDA) in 15% of patients with MMD, which is significantly higher than that in the general population. 19 MGDA is a rare congenital deficiency of the optic disc characterised by an enlarged, funnel-shaped excavation of the posterior pole involving the hypogenetic optic disc, which resembles a morning glory flower. Among 13 cases with MMD-associated MGDA, three (23.1%) patients were found to have midline cranial defects, two (15.4%) had meningoencephalocele and one (7.7%) patient had duplication of the pituitary stalk.…”
Section: Cephalic Neurocristopathymentioning
confidence: 99%